Brief Rewarming Blunts Hypothermia-Induced Alterations in Sensation, Motor Drive and Cognition - Brazaitis, Marius; Paulauskas, Henrikas; Skurvydas, Albertas; Budde, Henning; Daniuseviciute, Laura; Eimantas, Nerijus (Frontiers in Physiology, 2016)
Abstract Background: It is well known that cold exposure experienced during occupational or recreational activities may adversely affect motor, cognitive performance and health. Most research has used prolonged passive external rewarming modalities and focused on the direct effects on the kinetics of physiological and psychological responses in hypothermic subjects. However, the brief whole body rewarming effects on physiological and psychological responses in parallel with functional consequences on cognitive and neurophysiological functions have not been investigated. This study explores these effects in twelve healthy young men. Methods: Subjects (20±1 years) participated in 4 randomized trials, which were designed to compare the effects of whole-body brief (5-min) rewarming in 37°C water with rewarming for the same duration in 24°C (air) thermoneutral environment in mildly hypothermic subjects. After each rewarming, indicators of neuromuscular function (reflexes, central activation ratio, electromyography of exercising muscle, and contractile properties of calf muscles) and cognitive function (attention, simple motor speed, and information processing speed) were assessed. Results: Compared to rewarming in thermoneutral environment, after brief rewarming in 37°C water significantly lower metabolic heat production (206±33.4 versus 121.9±24.3 W•m2, P<0.01), heart rate (76±16 versus 60±12 b•min-1, P<0.01), cold strain (6.4±3.1 versus 5.3±2.7, P<0.01), improved thermal comfort and induced cessation of shivering was found. Electrically induced maximum torque amplitudes increased (P100, 102.8±21.3 versus 109.2±17.5 Nm and PTT100, 83.1±17.1 versus 92.7±16.0 Nm, P<0.05), contraction half-relaxation time decreased (599.0±53.8 versus 589.0±56.3 ms, P<0.05), and Mmax-wave latency shortened (17.5±2.2 versus 15.6±2.0 ms, P<0.05) after 37°C water rewarming. Unlike rewarming in thermoneutral environment, 37°C water rewarming blunted the hypothermia-induced alterations in neural drive transmission (4.3±0.5 versus 3.4±0.8 mV H-reflex and 4.9±0.2 versus 4.4±0.4 mV V-wave, P<0.05), which increased central fatigue during a 2-min maximum load (P<0.05). Furthermore, only in brief warm water rewarming cerebral alterations were restored to the control level and it was indicated by shortened reaction times (P<0.05). Conclusions: Brief rewarming in warm water rather than the same duration rewarming in thermoneutral environment blunted the hypothermia-induced alterations for thermoregulation, sensation, motor drive and cognition, despite the fact that rectal and deep muscle temperature remained lowered.